2021
DOI: 10.3390/ijms222010984
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex Targeting in the Fight against Viruses: An Update

Abstract: G-quadruplexes (G4s) are noncanonical nucleic acid structures involved in the regulation of key cellular processes, such as transcription and replication. Since their discovery, G4s have been mainly investigated for their role in cancer and as targets in anticancer therapy. More recently, exploration of the presence and role of G4s in viral genomes has led to the discovery of G4-regulated key viral pathways. In this context, employment of selective G4 ligands has helped to understand the complexity of G4-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 113 publications
0
59
0
Order By: Relevance
“…Naturally, not only the human genome contains GQ-forming sequences; several viral genomes were analyzed, and the potential targets of the antiviral therapy were reviewed by Ruggiero [ 147 , 148 ]. The genome of the SARS-CoV-2 virus has also been analyzed from this point of view [ 149 ], and some of the predicted viral GQs were experimentally found [ 148 , 150 ].…”
Section: Pressure Effect On Some Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, not only the human genome contains GQ-forming sequences; several viral genomes were analyzed, and the potential targets of the antiviral therapy were reviewed by Ruggiero [ 147 , 148 ]. The genome of the SARS-CoV-2 virus has also been analyzed from this point of view [ 149 ], and some of the predicted viral GQs were experimentally found [ 148 , 150 ].…”
Section: Pressure Effect On Some Biomoleculesmentioning
confidence: 99%
“…Naturally, not only the human genome contains GQ-forming sequences; several viral genomes were analyzed, and the potential targets of the antiviral therapy were reviewed by Ruggiero [ 147 , 148 ]. The genome of the SARS-CoV-2 virus has also been analyzed from this point of view [ 149 ], and some of the predicted viral GQs were experimentally found [ 148 , 150 ]. In my previous papers I analyzed three GQ-forming sequences of the Hepatitis B virus [ 65 , 151 ], and genomic analysis suggested the possible GQ formation of these sequences [ 152 , 153 ].…”
Section: Pressure Effect On Some Biomoleculesmentioning
confidence: 99%
“…Another potential target is the G4 structural motif, which has been recently identified in the pre-core promotor region of cccDNA through pulldown assays to the G4-binder DHX36 [ 120 ]. G4 structures, which form in GC-rich regions of RNA and DNA, have been identified in a variety of nucleic acids including untranslated regions of mRNAs, human telomeres, and genomes of viruses belonging to most Baltimore classes [ 121 , 122 ].…”
Section: Recent Developments In Dna and Mrna Detection For Living Cellsmentioning
confidence: 99%
“…For this reason, they are also of major interest in the context of the current pandemic caused by the infectious pathogen SARS-CoV-2, whose genome has been shown to contain G4-compatible regions [ 4 , 5 , 6 , 7 , 8 ]. Interesting and recent reviews on the antiviral possibilities offered by G4 can be found in literature [ 9 , 10 , 11 ]. G4s are also involved in some neurological diseases, such as alpha-thalassemia or X-linked intellectual disability syndrome, in which they are positively or negatively involved in a cascade of gene expression regulation [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%